RESEPSI KULTURAL MASYARAKAT PADANGRATU PADA TRADISI ZIKIR FIDA’ (Kajian Living Qur’an) - Bahagya, Erick; Ahmad Bastari; Beko Hendro (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2026)
This study examines the cultural reception of the Zikir Fida' Tradition by the community of Padangratu, Central Lampung, through the Living Qur’an approach. The main focus of the research is to understand how the community interprets and practices verses of the Qur'an, specifically Q.S. Al-Ahzab (33):41 and Q.S. Ar-Ra'd (13):28, within this ritual. Using qualitative methods such as observation, interviews, and documentary studies. this research analyzes the functions of the tradition based on Robert K. Merton’s Structural Functionalism theory. The results show that zikir Fida' not only serves a manifest function as a means of seeking redemption (fida') from hellfire but also has latent functions as a strengthener of social solidarity, a medium for emotional catharsis, and a reinforcement of spiritual beliefs. This tradition reflects the dialectic between sacred texts and local contexts, where the Qur'an is brought to life through meaningful communal practice. The study concludes that zikir Fida' is a complex form of cultural reception and a functional mechanism in maintaining the socio-spiritual balance of the community. Keywords : Zikir Fida', Living Qur'an, Cultural Reception, Structural Functionalism, Padangratu Community.